Kiss: A Web Application for Key Record Tracking Using Server-Side Scripting Language and Robust Data Storage - Hasimahwati Abu Yamin (Human Sustainability Procedia, 2018)
KKS2 is an educational institution equipped with rooms, labs and workshops ranging from Diploma in Photovoltage Solar Technology, Information Technology, Architecture, and Electrical Installation courses. These courses are using different rooms to adequate the lessons. Therefore, an efficient system to record and track keys to these rooms is crucial to maintain comfortable working environments. Keys are kept organized and easy to access whereas the locations can be monitored online. Whilst an approach to solve a problem often addressed using methods, procedures, frameworks, technical apparatus and many others, the researcher is introducing KISS. KISS can record and tracked keys virtually as it is using dynamic server-side scripting language. KISS introduces better ways to manage problems that arises prior to it because of keys displacement because the basic process of borrow and return keys can be checked online by users. Thus, users can retrieve and search any information about and on the keys whereabouts 24/7 on their fingertips. In addition, expanding user interaction within other institutions also possible through collaboration because KISS promised robust database storage. Also, HCSDLC model is used to develop the system as it is more flexible to maintain as each phase is organized with suitable activities towards fast and efficient system development.